Evaluasi Sistem Pengendalian Internal Antarlembaga ZISWAF: Implikasi bagi Kesejahteraan Umat - Diana Septiani; Rafi Hamdallah; Takrimatul Maulidiyah (Teewan Journal Solutions, 2024)
This study aims to examine the internal system implemented by institutions related to ZISWAF management in general and its implications for the welfare of the people. The research method used is qualitative by using the theory of evaluation, Internal Control System (ISS), and the theory of people's welfare. The method is used by examining several relevant relevant so that data is obtained in the form of tables and conclusions. The results of the research are found comparative data sampled from Baznas, BWI, and LAZ with indicators including institutional structure, financial data, achievements, along with the necessary evaluation. The data is then associated with the role of ZISWAF in the implication of improving the welfare of the people.